Financial literacy, moderation and financial spending among youth - Ramlee, Roslily; Syed Mohd Zain, Sharifah Raihan; Wan Husain, Wan Rohaida; Jan, Muhammad Tahir (2019)
This paper investigates the practice of moderation (wasatiyyah concept) among the Malaysian university students in their financial decision making. Based on extant literature, we have discovered that there is massive problem in financial prudence of Malaysian university students. To this end, questionnaire was developed with several questions on wasatiyyah, financial literacy, materialism, and financial decisions. The data collected from the Malaysian university students were analysed using various analyses, such as exploratory factor analysis, confirmatory factor analysis, and structural equation modelling. It was found that wasatiyyah partially mediate the influence of materialism and financial literacy on students’ financial decisions. Within this domain, the paper is expected to offer fresh insight into the level at which the Malaysian university students are practicing wasatiyyah/moderation in their daily financial decisions. Moreover, relevant authorities, such as National Higher Education Fund Corporation (PTPTN), Bank Negara’s Central Credit Reference Information System (CCRIS), and Credit Counselling and Debt Management Agency (AKPK), could use this study as a reference point when making pertinent decisions.